2021
DOI: 10.3390/ijms22115783
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Adrenergic Receptors in Metabolic Therapies for Heart Failure

Abstract: The heart has a reduced capacity to generate sufficient energy when failing, resulting in an energy-starved condition with diminished functions. Studies have identified numerous changes in metabolic pathways in the failing heart that result in reduced oxidation of both glucose and fatty acid substrates, defects in mitochondrial functions and oxidative phosphorylation, and inefficient substrate utilization for the ATP that is produced. Recent early-phase clinical studies indicate that inhibitors of fatty acid o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 415 publications
(542 reference statements)
0
11
0
Order By: Relevance
“…These catecholamines regulate blood pressure by binding to the α-adrenergic receptors present in blood vessels. Studies have shown that they have better affinity to α2-than α1 -adrenergic receptors ( Pecquery and Giudicelli, 1982 ; Perez, 2021 ). Moreover, the α2 subtype genes knock-out study has shown that their vasopressor activity is mediated probably through α2A as the effect of norepinephrine on arterial contraction was abrogated in α2A − mouse but not in α2B − or α2C − mouse ( Link et al, 1995 ; Link et al, 1996 ; Altman et al, 1999 ; Philipp et al, 2002 ).…”
Section: Targeting Adrenergic Receptors In Shockmentioning
confidence: 99%
“…These catecholamines regulate blood pressure by binding to the α-adrenergic receptors present in blood vessels. Studies have shown that they have better affinity to α2-than α1 -adrenergic receptors ( Pecquery and Giudicelli, 1982 ; Perez, 2021 ). Moreover, the α2 subtype genes knock-out study has shown that their vasopressor activity is mediated probably through α2A as the effect of norepinephrine on arterial contraction was abrogated in α2A − mouse but not in α2B − or α2C − mouse ( Link et al, 1995 ; Link et al, 1996 ; Altman et al, 1999 ; Philipp et al, 2002 ).…”
Section: Targeting Adrenergic Receptors In Shockmentioning
confidence: 99%
“…32 An excellent recent review thoroughly examined the adrenergic regulation of metabolic substrate utilization in the heart. 35 Here, we describe the effects of a1-AR and b-AR activation on mitochondrial biogenesis, dynamics, calcium handling, and OXPHOS in uninjured and failing cardiomyocytes (summarized in Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Beta-2 receptors are located in human bronchial smooth muscle cells, vascular smooth muscle cells and cardiac myocytes, albeit at a lower expression density compared to beta-1 receptors ( Brodde, 2008 ; Perez, 2021 ). While selective β-2 antagonists are not in clinical use in humans, a beta-2 blocking agent called butoxamine has been shown to decrease blood pressure and heart rate and increase airway resistance in animal studies ( Letts et al, 1983 ; Beiermeister et al, 2010 ).…”
Section: Adrenergic Modulationmentioning
confidence: 95%